Effect of water vapor on the reduction kinetics of hematite powder by hydrogen-water vapor in different stages - Mao X.-D.; Hu X.-J.; Fan Y.-W.; Chou K-.C. (Journal of Mining and Metallurgy. Section B: Metallurgy, 2023)
The powder of the hematite sample was isothermally reduced with a hydrogen-water vapor gas mixture at 1023K-1273K. The results indicate that the overall reduction process of hematite can be divided into three stages (Fe2O3-Fe3O4-FeO-Fe) each of which should be investigated. At 1023K, the average reaction rate decreased by 53.6% in stage 1 when the water vapor content of the reaction gas increased from 0% to 50%, and it decreased by about 77.2% in stage 2. However, in stage 3, when the water vapor content increased only from 0% to 20%, it decreased by about 78.1%. The results also show that the influence of water vapor on the reduction reaction increases with increasing reaction temperature in all stages of the reduction reaction. The microstructure of the reduction products showed that they still had some holes; that did not seriously block the channel for hydrogen diffusion. Various models were considered to further clarify the influence of water vapor in the reduction stage The range of apparent activation energy of the different stages obtained by the model fitting was about 20-70 kJ/mol, which also confirmed the absence of the solid-state diffusion phenomenon.